Suicide attempters with Borderline Personality Disorder show differential orbitofrontal and parietal recruitment when reflecting on aversive memories. (October 2016) - Silvers, Jennifer A.; Hubbard, Alexa D.; Chaudhury, Sadia; Biggs, Emily; Shu, Jocelyn; Grunebaum, Michael F.; Fertuck, Eric; Weber, Jochen; Kober, Hedy; Carson-Wong, Amanda; Brodsky, Beth S.; Chesin, Megan; et al.
Abstract: Suicidal behavior and difficulty regulating emotions are hallmarks of Borderline Personality Disorder (BPD). This study examined neural links between emotion regulation and suicide risk in BPD. 60 individuals with BPD (all female, mean age = 28.9 years), 46 of whom had attempted suicide, completed a fMRI task involving recalling aversive personal memories. Distance trials assessed the ability to regulate emotion by recalling memories from a third-person, objective viewpoint. Immerse trials assessed emotional reactivity and involved recalling memories from a first-person perspective. Behaviorally, both groups reported less negative affect on Distance as compared to Immerse trials. Neurally, two sets of findings were obtained. The first reflected differences between attempters and non-attempters. When immersing and distancing, attempters showed elevated recruitment of lateral orbitofrontal cortex, a brain region implicated in using negative cues to guide behavior. When distancing, attempters showed diminished recruitment of the precuneus, a region implicated in memory recall and perspective taking. The second set of findings related to individual differences in regulation success – the degree to which individuals used distancing to reduce negative affect. Here, we observed that attempters who successfully regulated exhibited precuneus recruitment that was more similar to non-attempters. These data provide insight into mechanisms underlying suicide attempts in BPD. Future work may examine if these findings generalize to other diagnoses and also whether prior findings in BPD differ across attempters and non-attempters.